IMPROVING STUDENTS’ ACHIEVEMENT IN SPEAKING THROUGH TWO STAY TWO STRAY STRATEGY - Dita Masyitah Sianipar; Sumarsih (Universitas Negeri Medan, 2013)
This study deals with the way to improve students’ achievement in speaking particularly through Two Stay Two Stray Strategy. This study was conducted by using classroom action research. The subject of of the research was class X-AP SMK Swasta Harapan Danau Sijabut in Asahan Regency that consisted of 34 students. The research was conducted in two cycles consisted of three meetings in each cycle. The instruments of collecting data for quantitative data used Speaking Test and instrument for analysis of qualitative data used observation, interview and questionnaire sheet. Based on the speaking test score, students’ score kept improving in every test. In the test I the mean was 61,47, in the test II the mean was 67,41 and the test III the mean was 78,52. Based on observation sheet and questionnaire sheet, it was found that teaching learning process run well and lively. Students were active and interest in speaking. The using of Two Stay Two Stray Strategy is significantly improved students’ achievement in speaking.